REVISION AND RE-DOCUMENTATION OF M. AIROLDI'S SPECIES OF LITHOPHYLLUM FROM THE TERTIARY PIEDMONT BASIN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
The species originally attributed by Airoldi (1932) to the genus Lithophyllum (L. perrandoi, L. ligusticum, L. personatum and L. desitum) are here re-examined on the basis of the original material, original descriptions and illustrations. L. perrandoi and L. ligusticum are considered to be conspecific and questionably retained in the genus Lithophyllum. We give priority to the name ?L. perrandoi Airoldi to honour the priest Don Perrando, who collected most of the fossils conserved in the Dip.Te.Ris of Genova. L. personatum and L. desitum do not belong to the genus Lithophyllum as presently circumscribed. L. personatum Airoldi is a female/carposporangial plant of a mastophoroid species resembling Spongites fruticulosus Kützing, and therefore we retain a dubitative identification with the new combination ?Spongites personatus (Airoldi). L. desitum is here placed in the genus Mesophyllum under the new combination Mesophyllum desitum (Airoldi). On the basis of its vegetative and reproductive features, M. desitum comb. nov. is here considered conspecific with Mesophyllum obsitum Airoldi. Pdf
Keywords: Corallinales; Airoldi type collection; Taxonomy; Stratigraphy; Lithophyllum; Spongites; Mesophyllum